PENGARUH PEMBELAJARAN JARAK JAUH TERHADAP MOTIVASI BELAJAR SISWA KELAS IV SD SE-KECAMATAN PADAMARA TAHUN AJARAN 2021-2022 - Laras Nur Tantifah; Rokhmaniah Rokhmaniah; Wahyudi Wahyudi (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2022)
AbstractThe study aimed to examine the influence of distance learning on learning motivation to fourth grade students of public elementary schools in Padamara sub-district in academic year of 2020/2021. It used quantitative design with correlation research methods. The samples were 192 fourth grade students in 9 elementary schools in Padamara sub-district. The sampling method used probability sampling technique of random sampling. The data collection technique used questionnaires. The data analysis used simple correlation test and a simple linear regression test using the SPSS 21 application with a significance level of 5%. The result indicated that the rcount values between distance learning and learning motivation were 0.132<0.138 on the students and -0.295<0.632 on the teacher. It meant that there could not find significant influence of distance learning variables on students’ learning motivation variables. To the students, the distance learning contributed 1.79% on students’ learning motivation and the remaining 98.21% was influenced by other factors. To the teacher, the effective contribution value was 8.7%, and the remaining 91.3% was influenced by other factors. It concludes that distance learning does not have significant influence on the learning motivation to fourth grade students of public elementary schools in Padamara sub-district in academic year of 2020/2021. Keywords: distance learning, learning motivation  Penelitian ini bertujuan membuktikan adanya pengaruh pembelajaran jarak jauh terhadap motivasi belajar siswa kelas IV SD se-Kecamatan Padamara tahun ajaran 2021-2022. Desain penelitian yang digunakan adalah kuantitatif dengan metode penelitian korelasi. Sampel penelitian yaitu 192 siswa kelas IV dari 9 sekolah dasar di Kecamatan Padamara, diambil secara acak dengan teknik simple random sampling. Teknik pengumpulan data menggunakan angket. Analisis data yang digunakan yaitu uji korelasi sederhana dan uji regresi linier sederhana menggunakan aplikasi SPSS 21 dengan taraf signifikansi 5%. Hasil korelasi antara pembelajaran jarak jauh dan motivasi belajar dari pihak siswa mendapat nilai r hitung sebesar 0.132<0.138, dan hasil korelasi dari pihak guru, memperoleh nilai r hitung sebesar -0.295<0.632. Nilai sumbangan efektif pembelajaran jarak jauh terhadap motivasi belajar dari pihak siswa sebesar 1.79%, sedangkan nilai sumbangan efektif dari pihak guru sebesar 8.7%,. Kesimpulannya adalah tidak terdapat pengaruh signifikan pembelajaran jarak jauh terhadap motivasi belajar siswa kelas IV SD se-Kecamatan Padamara tahun ajaran 2021-2011 Kata kunci: pembelajaran jarak jauh, motivasi belajar